Analysis of Imagery in the Poem "DADDY" by Sylvia Plath - Panjaitan, Indra Purnawan; Hamka, Nurhadi (Linguistic, English Education and Art (LEEA) Journal, 2023)
The aim of this study to describe the image contained in the poem "Daddy" by Sylvia Plath. The method used in this research is qualitative descriptive. Data collection used the technique of reading logs of the poem "Daddy" by Sylvia Plath. The research result were visual imagery, auditory imagery, pictures No aesthetic and magical. Conclusion from results of imagery analysis carried out on the poem "Daddy" by Sylvia Plath is that the most dominant image is visual imagery. Keywords: Analysis, Imagery, Literature, Poetry